(untitled) (Journal of Medical Sciences, 2023)
Objective: This questionnaire based study aimed to determine the most common method of replacing missing teeth by patients attending University Dental Clinics in Sebha (Libya). Materials and Methods: (Questionnaire) A total of 80 patients attending University Dental Clinics in Sebha were participated in this study. A self-administered questionnaire was distributed to 80 patients. Data were analyzed. Criteria included age of 20 years and above with one or more missing teeth except for third molars. Results: A response from 80 participants were obtained 22 (27%) male and 58 (73%) female. Female patients preferred to replace their missing teeth with dental implant were more than male (73%) vs (27%) respectively. Age group (40-60) 65% was more significantly preferred dental implant than age (20-60) 35%. Anterior region was more replaced than the posterior respectively (62%) vs (38%). Male (40- 80) years (40%) preferred more to replace their missing teeth with dental implant than the patients aged (20-40) years (18%). Patients (40-60) years (47%) were more than patients aged (60-80) (27%) & (20-40) (26%). For final restoration, crowns (68%) were more likely to be employed than bridges (32%) in male patients. Moreover, crowns (69%) were more employed than bridges (31%) in female patients. No significant difference between zirconium and porcelain (56%) and (55%) respectively in male patients. In contrast, there were significant difference between zirconium and porcelain in female patients (77%) versus (23%) respectively. Conclusion: Implant were found to be most widely employed in female patients. More female patients were employed crowns and bridges than male patients. Patients aged (60-80) year were the most common requested to have dental implant. Most of patients preferred to have implant in upper jaw when compared to the lower jaw. Zirconium more commonly employed than porcelain.